Catalytic palladium nanoreactor design for the Suzuki cross coupling reaction - Hayman, Charlotte L (2023)
This report investigates the design of a recyclable palladium nanocatalyst to be utilised in the Suzuki cross coupling reaction. Palladium nanoparticles (PdNPs) were combined with graphitised nanofibers (GNF) and then developed to improve its properties as a catalyst. Different methods of deposition were employed, including an innovative use of magnetron sputtering, to attempt to improve catalyst performance. Other approaches such as changing the structure of the carbon support were also used to test the capabilities of this promising material. Magnetic Iron NPs (FeNPs) were also employed as a method of improving the recyclability of the PdNPs, making the extraction process between cycles easier and quicker. Each catalyst was tested for its activity and recyclability using a simple Suzuki cross coupling reaction, and utilised in up to five cycles. Conversion of the product was determined by 1H NMR. High resolution transmission electron microscopy (HRTEM) was used to determine particle size and distribution, both before and after reactions. This was essential for determining which methods could be used to improve the performance and recyclability of the catalyst. Thermal gravimetric analysis (TGA) was used to determine metal loadings which in turn could produce quantitative measurements of activity, turnover number (TON) and turnover frequency (TOF). In total, ten variants of a PdNPs@GNF catalyst were synthesised and tested to determine the most effective one for Suzuki cross couplings and obtained a wide variety of results. It became evident that adding a hydrogenation step to the procedure was essential, as all the catalysts which involved this step had dramatically advanced performances (yields as high as 97 %). This excellent result opens up an exciting opportunity for this catalyst to undergo further testing to extend its use to more challenging starting materials and reactions. These exciting results proved the potential of PdNPs@GNFs as catalysts and were used to determine the best way of synthesising this material. This investigation involved making structural changes to this material to design an active recyclable catalyst for Suzuki cross coupling reactions.